Network pharmacology study of traditional Chinese medicines for stroke treatment and effective constituents screening. (5th October 2019) - Ren, Liwen; Zheng, Xiangjin; Liu, Jinyi; Li, Wan; Fu, Weiqi; Tang, Qin; Wang, Jinhua; Du, Guanhua
Abstract: Ethnopharmacological relevance: Stroke is one of the most frequent causes of death and disability. So far there are no effective preventives or treatments. The therapeutic system of traditional Chinese medicines (TCMs) has been in use for several thousand years and still affords a valuable resource for today's clinicians in preserving health. Materials and methods: We had collected the Chinese medicinal formulae and then commonly used single herbs or drug combinations were analyzed through data mining. The ingredients from the top 30 frequently used herbs which have good druggability and blood-brain barrier permeability were collected as a natural product library. Targets of the related ingredients were predicted using various databases and analyzed by GO and KEGG pathway mapping. The potential stroke targets were validated in the market or from clinical trials, and used to establish molecular docking, HipHop and SBP models to screen new compounds for multi-target activity. Lastly, in vitro experiments with models for oxygen and glucose deprivation and reperfusion (OGDR) were conducted to test the activities of compounds identified by screening. Results: A total of 1679 Chinese medicinal formulas were selected and their prescription rules were analyzed. 4277 compounds were from the top 30 herbs and 3560 molecules were filtered to build the natural product library. The ingredient-target network, target-disease network and target-target interaction network were established to explain the characteristics and mechanisms of the TCMs. Thirty-one molecules were selected to have multi-target activity on targets of stroke via virtual screening. Five of these had already been reported to have therapeutic effects on stroke. Three of the eight compounds which have been examined showed protective effects on OGDR model. Conclusions: This paper details a novel strategy for exploring the characteristics and mechanisms of herbal medicines from a systematic standpoint in an attempt to identify those affecting specific target pathways related to stroke. Using this methodology on our natural products library, we found a number of lead candidates with multi-target activity. Graphical abstract: Image 1